Microbiology and fermentative losses of rehydrated whole plant silage harvested at high maturity - Anjos, Victor Federico Leal dos (2023)
The whole plant corn silage (WPCS) is the most used roughage in the diet of beef and dairy cattle in Brazil. The use of technologies in the making of silage has been increasing in recent years in order to ensure a more efficient harvest and a good fermentation standard for the silos. However, in some regions of the country, the rainfall deficit generates water stress in plants, altering the chemical quality and profile of carbohydrates available for fermentation. On the other hand, the presence of rain at the time of harvesting can also cause delays. In many cases, harvesting maize plants with high dry matter leads to considerable fermentation losses in the silage. Rehydrating the plant according to some researchers and field technicians can improve the conservation of plants with high DM. The advantages and the way that corn grain rehydration should be done in order to take better use of the starch is well described in the literature. However, there are no studies evaluating how SMPI rehydration can improve the fermentative aspects of the silo environment. In this sense, the objective of this study was to evaluate the losses and fermentative profile of silages with DM above the recommended level and silages harvested with high DM and which received water addition in order to reduce the DM to the recommended standard. Five harvests were performed at 7-day intervals each, where in the first harvest the mass was ensiled without adding water (34.7%), in the other harvests the materials were ensiled with the respective DM for the harvest (40.7; 46.9, 49.5 and 54.2%) and ensiled with the addition of water (34.9; 35.5; 34.0; 33.7%) so that DM returned close to that found in the first harvest. The materials were ensiled in experimental silos (20 L buckets) containing 2 kg of sand at the bottom separated by a screen and cloth in order to measure the production of effluents (EL) and equipped with lids for complete sealing. The storage time was 90 days. The treatments were arranged in a factorial scheme with four replications (2*4+1) being 2 with and without water addition; 4 DM at the time of harvest and 1 the positive control treatment. The data were analyzed using the SAS MIXED procedure. Fermentative losses, pH, lactic acid, volatile fatty acids, ethanol, microorganisms, aerobic stability (A.E), density, mean particle distribution, water holding capacity (WHC) and bromatological were evaluated. The pH of the materials that received the addition of water were lower compared to the treatments without the addition of water and did not differ from the positive control. Lactic acid production and lactic acid fermenting bacteria (LAB) counts were also higher in rehydrated treatments. There was no difference between any of the treatments for clostridia. The higher the DM at the time of harvest, the greater the addition of water, which led to greater losses by effluents, the treatment with DAE 135 and 36.8% DM obtained the highest losses by effluents. Density was also altered during rehydration, plants with higher dry matter linearly decreased density, while rehydrated treatments maintained initial density, only the treatment with DAE 135 and 36.8% DM differed. The average rehydrated treatments also showed higher A.E., but no treatment showed good A.E. Those with high DM were losing WHC. In conclusion, the results suggest that adding water can be a good strategy to reduce losses and improve the fermentative pattern and maize plants harvested with high DM. However, not every plant has the capacity to retain additional water, materials with DM above 55% showed greater production of effluents, which generates greater losses and greater environmental risk.